2013
DOI: 10.47678/cjhe.v43i2.2403
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary doctoral research supervision: A scoping review

Abstract: This scoping literature review examines the topic of interdisciplinary doctoral research supervision. Interdisciplinary doctoral research programs are expanding in response to encouragement from funding agencies and enthusiasm from faculty and students. In an acknowledgement that the search for creative and innovative solutions to complex problems is best addressed through interdisciplinary collaborations, research-intensive universities are increasingly encouraging interdisciplinary projects and programs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…First, KI does not come easily. It is worth mentioning that the roles of mentors in the interdisciplinary exploration of doctoral students are not fully understood (Lindvig, 2018;Lyall et al, 2015;Vanstone et al, 2013). Therefore, we suggest that educators actively try to enhance KI relations.…”
Section: Recommendationsmentioning
confidence: 84%
See 2 more Smart Citations
“…First, KI does not come easily. It is worth mentioning that the roles of mentors in the interdisciplinary exploration of doctoral students are not fully understood (Lindvig, 2018;Lyall et al, 2015;Vanstone et al, 2013). Therefore, we suggest that educators actively try to enhance KI relations.…”
Section: Recommendationsmentioning
confidence: 84%
“…Besides this, the mentorship including student-supervisor and student-student mentoring plays an important role in interdisciplinary learning and engagement of students (Ryser et al, 2009;Vanstone et al, 2013). Moreover, it has been suggested that participants from neighbouring disciplinary fields might integrate more knowledge compared to participants from distant disciplinary fields (Porter & Rafols, 2009).…”
Section: Intervening Factors On Kt and Ki Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-advisors may be needed to provide the additional content expertise or the creation of an interdisciplinary committee. For a review of the work on interdisciplinary graduate supervision, see [9] . Where a number of studies have investigated the role of the graduate advisor for interdisciplinary students [9][10][11] , few investigate the role of the graduate student's committee.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For a review of the work on interdisciplinary graduate supervision, see [9] . Where a number of studies have investigated the role of the graduate advisor for interdisciplinary students [9][10][11] , few investigate the role of the graduate student's committee. A graduate student's committee generally comprises of 4-5 members who "work with them on developing a program plan, preparing and taking comprehensive exams, planning and executing a study, and completing the dissertation" [12] .…”
Section: Literature Reviewmentioning
confidence: 99%